ISOLATION AND CHARACTERIZATION OF NITRIFYING BACTERIA BACILLUS ANTHRACIS MTCC NO. 2104 FROM LONGSTANDING CULTIVATION OF BT COTTON RIZHOSPHERE SOIL - RAAGINI, P. SIVA; LAKSHMI , K. VIJAYA; K. USHASRI, (The Bioscan, 2013)
In the present study, an attempt has been made to isolate the Nitrifying bacteria from the total of eleven bacteria of rhizosphere soil of Bt cotton. Among the eleven isolates, six isolates were positive in primary screening for nitrifying activity. The cultures of these six isolates were secondary screened, by a micro titer system based on the most probable number (MPN) method with an increased accuracy. Finally, one isolated bacteria which shows maximum activity labeled as Bt rhizosphere soil (Btrs7) was selected and characterized. This is further conformed by IMTECH, Chandigarh and identified as Bacillus anthracis with MTCC no 2104.